Judges 1: a commentary on Judges 1:1-10:5 - Smith, Mark S., 1955- (Hermeneia--a critical and historical commentary on the Bible., 2021)
This groundbreaking volume presents a new translation of the text and detailed interpretation of almost every word or phrase in the book of Judges, drawing from archaeology and iconography, textual versions, biblical parallels, and extrabiblical texts, many never noted before. Archaeology also serves to show how a story of the Iron II period employed visible ruins to narrate supposedly early events from the so-called "period of the Judges." The synchronic analysis for each unit sketches its characters and main themes, as well as other literary dynamics. The diachronic, redactional analysis shows the shifting settings of units as well as their development, commonly due to their inner-textual reception and reinterpretation. The result is a remarkably fresh historical-critical treatment of 1:1-10:5.--Publisher's description.